2012
DOI: 10.1103/physrevc.85.015807
|View full text |Cite
|
Sign up to set email alerts
|

Proton fraction in the inner neutron-star crust

Abstract: Monte Carlo simulations of neutron-rich matter of relevance to the inner neutron-star crust are performed for a system of A = 5, 000 nucleons. To determine the proton fraction in the inner crust, numerical simulations are carried out for a variety of densities and proton fractions. We concludeas others have before us using different techniques-that the proton fraction in the inner stellar crust is very small. Given that the purported "nuclear pasta" phase in stellar crusts develops as a consequence of the long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(120 citation statements)
references
References 37 publications
13
107
0
Order By: Relevance
“…Although a robust correlation between the electric dipole polarizability and the neutron skin thickness was found [19], based on the droplet model it was shown that the correlation becomes significantly stronger for the product of the electric dipole polarizability and the nuclear symmetry energy coefficient J [20]. The correlation was indeed found to be very strong, but current uncertainties in the determination of J hinder the determination of the neutron skin thickness of 208 Pb.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Although a robust correlation between the electric dipole polarizability and the neutron skin thickness was found [19], based on the droplet model it was shown that the correlation becomes significantly stronger for the product of the electric dipole polarizability and the nuclear symmetry energy coefficient J [20]. The correlation was indeed found to be very strong, but current uncertainties in the determination of J hinder the determination of the neutron skin thickness of 208 Pb.…”
Section: Resultsmentioning
confidence: 98%
“…Following the high-resolution measurement carried out at RCNP [12], two systematic studies of the electric dipole polarizability of 208 Pb were performed using a large set of nuclear EDFs [19,20]. Although a robust correlation between the electric dipole polarizability and the neutron skin thickness was found [19], based on the droplet model it was shown that the correlation becomes significantly stronger for the product of the electric dipole polarizability and the nuclear symmetry energy coefficient J [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently is has been shown that the dipole polarisability (how the energy of the nucleus changes in an external field) is correlated to the dipole response, the neutron skin and the slope of the EoS symmetry energy [43,44]. Several recent works also relate the neutron skin and the density dependence of the symmetry energy [45,46].…”
Section: Nuclear Dynamicsmentioning
confidence: 99%